2000
DOI: 10.1001/archneur.57.9.1347
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function of Patients With Nasopharyngeal Carcinoma With and Without Temporal Lobe Radionecrosis

Abstract: Radiotherapy for nasopharyngeal carcinoma seemed to have adverse but insignificant effects on the cognitive functions of the patients. However, for patients who developed temporal lobe necrosis after radiotherapy, memory, language, motor ability, and executive functions were significantly impaired, although their general intelligence remained relatively intact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 34 publications
2
82
2
Order By: Relevance
“…In addition, a number of neural psychology test studies have revealed that patients with cranial irradiation experienced a decrease in cognitive function (24). Previous studies have been limited to the WM due to radiation sensitivity.…”
Section: Mni Coordinate (Mm) ----------------------------------mentioning
confidence: 99%
“…In addition, a number of neural psychology test studies have revealed that patients with cranial irradiation experienced a decrease in cognitive function (24). Previous studies have been limited to the WM due to radiation sensitivity.…”
Section: Mni Coordinate (Mm) ----------------------------------mentioning
confidence: 99%
“…Data on neurocognitive functioning in patients with head and neck cancer (HNC) are primarily limited to eight small studies [8][9][10][11][12][13][14][15]. Six studies [8][9][10][11][12][13] evaluated the neurocognitive effects of potential radiation-induced brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…Six studies [8][9][10][11][12][13] evaluated the neurocognitive effects of potential radiation-induced brain injury. The study samples included only patients with either nasopharyngeal or paranasal sinus tumors, in which treatment entailed incidental radiation to normal brain tissue and thus the potential for direct radiation damage.…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al [35] reported that NPC patients with radiation-induced brain injury (RI) exhibited negative emotions, impaired cognitive function and quality of life (QOL). The accumulated studies showed that the radiation-induced functional impairments included the disorder of short-term memory [36], personality changes [37] and motor abilities [38], a marked anterograde memory impairment for verbal material [39], neuropsychological impairments in recent memory, immediate and delayed verbal recall, and immediate visual recall [40].…”
Section: Resultsmentioning
confidence: 99%